Donor source and post‐transplantation cyclophosphamide influence outcome in allogeneic stem cell transplantation for GATA2 deficiency. (27th September 2021) - Nichols‐Vinueza, Diana X.; Parta, Mark; Shah, Nirali N.; Cuellar‐Rodriguez, Jennifer M.; Bauer, Thomas R.; West, Robert R.; Hsu, Amy P.; Calvo, Katherine R.; Steinberg, Seth M.; Notarangelo, Luigi D.; Holland, Steven M.; Hickstein, Dennis D.
Summary: GATA2 deficiency was described in 2011, and shortly thereafter allogeneic hematopoietic stem cell transplantation (HSCT) was shown to reverse the hematologic disease phenotype. However, there remain major unanswered questions regarding the type of conditioning regimen, type of donors, and graft‐versus‐host disease (GVHD) prophylaxis. We report 59 patients with GATA2 mutations undergoing HSCT at National Institutes of Health between 2013 and 2020. Primary endpoints were engraftment, reverse of the clinical phenotype, secondary endpoints were overall survival (OS), event‐free survival (EFS), and the incidence of acute and chronic GVHD. The OS and EFS at 4 years were 85·1% and 82·1% respectively. Ninety‐six percent of surviving patients had reversal of the hematologic disease phenotype by one‐year post‐transplant. Incidence of grade III‐IV aGVHD in matched related donor (MRD) and matched unrelated donor recipients (URD) patients receiving Tacrolimus/Methotrexate for GVHD prophylaxis was 32%. In contrast, in the MRD and URD who received post‐transplant cyclophosphamide (PT/Cy), no patient developed grade III‐IV aGVHD. Six percent of haploidentical related donor (HRD) recipients developed grade III‐IV aGVHD. In summary, a busulfan‐based HSCT regimen in GATA2 deficiency reverses the hematologic disease phenotype, and the use of PT/Cy reduced the risk of both aGVHD and cGVHD.